Kinetics of catalytic oxidation of sodium ethyl mercaptide. (18th May 2020) - Zhan, Yuan-Yuan; Shi, Jie; Su, Meng-Jun; Luo, Yong; Chu, Guang-Wen; Zou, Hai-Kui; Chen, Jian-Feng
Highlights: The priority of O2 and RS − absorbed on the catalyst was explored. Two-layer adsorption structure was proposed by DFT calculations. The rate expression of the intrinsic kinetics was proposed. The corresponding statistic of the kinetics data was rigorously tested. Abstract: Catalytic oxidation of mercaptide is a significant way to eliminate waste emission of spent caustic and recycle the resource of caustic. However, the kinetics of mercaptide oxidation for spent caustic regeneration is still unclear, which hinders the reactor design. In this work, mechanism analyses and kinetics experiments were conducted to investigate the kinetics of homogeneous catalytic oxidation of sodium ethyl mercaptide. Ultraviolet visual spectra show that mercaptide ion is superior to oxygen molecule adsorbed on the catalyst, which is in accord with the simulations. Reaction mechanism of two-layer adsorption structure was proposed by density functional theory calculations. By applying the method of decoupling macroscopic kinetics and making pseudo-first-order fast reaction hypothesis, the rate expression of the intrinsic kinetics for the oxidation reaction of sodium ethyl mercaptide was proposed as - d C A dt = 6.84 × 10 10 exp ( - 29584 RT ) C A C B . A statistical test was carried out to verify the intrinsic kinetics data, showing that the kinetics data were overall reasonable.